Substandard job performance: development of a model and the examination of poor organizational performers - Levine, Pamela J., author; Heggestad, Eric D., advisor; Smith, Charles A. P., committee member; Thornton, Geroge C., III, committee member; Borrayo, Evelinn A., committee member (Colorado State University. Libraries, 2006)
While vast amounts of research and literature exist on the nature of effective job performance, the nature of ineffective job performance has been neglected. Therefore, the purpose of Study 1 was to develop a model of substandard job performance, defined as behaviors that fail to meet organizational expectations for success. A construct-oriented approach to model development was used, involving multiple rounds of data collection and revision. Initial model content was developed via a review of relevant literature. Additional feedback was collected from: (a) a web-based survey of managers, (b) a SME focus group, (c) comparison to existing performance models, (d) review by academicians specializing in performance/performance appraisal, and (e) managerial telephone interviews. The final model is organized into 2 broad domains, 11 content areas, 35 dimensions, and 218 behavioral indicators. In particular, the indicators provide specific examples of behavior characterized as errors of omission (the failure to engage in a desired behavior) and errors of commission (engagement in an undesirable behavior). The inclusion of both types of errors, in addition to the multiple levels of description, provides a detailed specification of substandard job performance, which can be used to aid the identification, understanding, and management of substandard job performance. The purpose of Study 2 was to evaluate the content validity of the model and to use the model to discern the nature of substandard performance in one organization. Specifically, 80 performance appraisal narratives from poor performers (employees on a performance improvement plan) were subjected to content analysis using the model developed in Study 1. The substandard performance issues found in the narratives were classified into the model's 35 dimensions, thus providing evidence in support of the model's content validity. Frequencies were examined at the dimension, content area, and domain levels for the entire set of 80 narratives as well as for narratives separated by work environment (i.e., corporate and retail). Overall, Study 2 provided a descriptive picture of substandard performance in one organization and compared substandard performance feedback in retail and corporate work environments. Implications and directions for future research are discussed.
Keywords: models; polls and surveys; focus groups; behavior; errors; feedback; studies; success; narratives; content analysis; violence; researchers; nonverbal communication; validity; stress; copyright; literature reviews; qualitative research